2009
DOI: 10.1029/2009gl040692
|View full text |Cite
|
Sign up to set email alerts
|

Using satellite radar backscatter to predict above‐ground woody biomass: A consistent relationship across four different African landscapes

Abstract: Regional‐scale above‐ground biomass (AGB) estimates of tropical savannas and woodlands are highly uncertain, despite their global importance for ecosystems services and as carbon stores. In response, we collated field inventory data from 253 plots at four study sites in Cameroon, Uganda and Mozambique, and examined the relationships between field‐measured AGB and cross‐polarized radar backscatter values derived from ALOS PALSAR, an L‐band satellite sensor. The relationships were highly significant, similar amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
172
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(183 citation statements)
references
References 25 publications
7
172
0
4
Order By: Relevance
“…In Africa, [21] created an ALOS PALSAR mosaic at 100-m spatial resolution to be used, among other applications, to map deforestation and agricultural encroachment upon the forest-savanna boundary. In their study within savanna landscapes, [22] identified strong relationships between AGWB and radar backscatter sensed by ALOS PALSAR, concluding that the approach was necessary and sufficient for monitoring and reporting of biomass baselines for REDD+ projects, and [23] similarly found ALOS PALSAR images to assist in quantifying deforestation at small scales in savanna woodlands in Mozambique. In Australia, [24] stressed the value of ALOS PALSAR data for quantifying the contribution of the woody component of tropical savannas to regional carbon stocks.…”
Section: Mapping Of Savanna Woodlands With Active Satellite Earth Obsmentioning
confidence: 99%
“…In Africa, [21] created an ALOS PALSAR mosaic at 100-m spatial resolution to be used, among other applications, to map deforestation and agricultural encroachment upon the forest-savanna boundary. In their study within savanna landscapes, [22] identified strong relationships between AGWB and radar backscatter sensed by ALOS PALSAR, concluding that the approach was necessary and sufficient for monitoring and reporting of biomass baselines for REDD+ projects, and [23] similarly found ALOS PALSAR images to assist in quantifying deforestation at small scales in savanna woodlands in Mozambique. In Australia, [24] stressed the value of ALOS PALSAR data for quantifying the contribution of the woody component of tropical savannas to regional carbon stocks.…”
Section: Mapping Of Savanna Woodlands With Active Satellite Earth Obsmentioning
confidence: 99%
“…The wavelength (λ), relative to the size of the scatterer affects interactions between the two. Longer wavelengths are more relevant in the detection of vegetation geometry due to their penetrative effects, resulting in volume scattering [30,31]. The wavelength interaction with canopy elements results in diffuse scattering, hence more energy returning to the sensor [32].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-polarized measurements (HV or VH) work better than co-polarized (HH or VV) in correlating σ 0 to AGB since the former accounts for canopy as opposed to ground components. By using dualpol SAR (both HH, HV), Mitchard et al [30] found a relationship between AGB and σ 0 . Additional studies by [34,35] combined SAR and Lidar to improve AGB models by eliminating the bias that can occur from too many large trees.…”
Section: Introductionmentioning
confidence: 99%
“…In particular in tropical forests, remote sensing data provides spatially consistent information for areas that are difficult to access. Synthetic Aperture Radar (SAR) data have been shown to be useful for AGB estimation across the landscape, e.g., [3][4][5][6][7]. Microwave signals have the capability to penetrate the vegetation profile, reflecting the three-dimensional vegetation structure, and are useful for weather-independent applications, as long wavelengths penetrate clouds.…”
Section: Introductionmentioning
confidence: 99%